2018
DOI: 10.29399/npa.21611
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Copy Number Variation by arrayCGH in Turkish Children and Adolescents Diagnosed with Autism Spectrum Disorders

Abstract: The development of whole-genome screening methodologies for the detection of copy number variations (CNVs), such as array-based comparative genomic hybridization (aCHG), provides a much higher resolution than karyotyping leading to the identification of novel microdeletion and microduplication syndromes often associated with an autism spectrum disease (ASD) phenotype. The aim of the study was to determine CNVs of patients with ASD by using array-based comparative genomic hybridization.Methods: Fifty-three pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thus, abnormalities in the Slit/Robo pathway are observed in these neuropsychiatric disorders. There is increasing evidence that suggest Slit2 is associated with some neuropsychiatric disorders, including MDD (Huls et al, 2020), AD (Li et al, 2015), Parkinson's disease (PD) (Lin and Isacson, 2006), TLE (Fang et al, 2010), and ASD (Perez et al, 2016;Gorker et al, 2018). Depression and anxiety are common psychiatric disorders, and their pathogenesis is not well-understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, abnormalities in the Slit/Robo pathway are observed in these neuropsychiatric disorders. There is increasing evidence that suggest Slit2 is associated with some neuropsychiatric disorders, including MDD (Huls et al, 2020), AD (Li et al, 2015), Parkinson's disease (PD) (Lin and Isacson, 2006), TLE (Fang et al, 2010), and ASD (Perez et al, 2016;Gorker et al, 2018). Depression and anxiety are common psychiatric disorders, and their pathogenesis is not well-understood.…”
Section: Discussionmentioning
confidence: 99%
“…Slit/Robo signaling also mediates other biological processes such as angiogenesis, leukocyte chemotaxis, cell proliferation, and tumor growth and progression (Borrell et al, 2012;Yuen and Robinson, 2013;Jiang et al, 2019). Increasing evidence suggests that disturbance in Slit/Robo signaling plays a role in several neuropsychiatric disorders, including Alzheimer's disease (AD), autism spectrum disorder (ASD), temporal lobe epilepsy (TLE), and major depressive disorder (MDD) (Fang et al, 2010;Li et al, 2015;Gorker et al, 2018;Bai et al, 2020). Bai et al found that the Slit2 protein could be a novel biomarker candidate through proteomics profiling of the cerebrospinal fluid (CSF) in patients with AD (Bai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This was the first report, in which molecular karyotyping techniques were successfully applied in ASD patients from Turkey. In the second study presenting CNVs of patients with ASD, a larger sample size was analyzed [Gorker et al, 2018]. A total of 53 patients were evaluated using array-CGH, and 8 (15%) patients had pathogenic CNVs or VUS (2 pathogenic and 7 VUS).…”
Section: Discussionmentioning
confidence: 99%